Perencanaan Strategis SI/TI Menggunakan Metode Ward and Peppard di Institusi Pendidikan (Studi Kasus: SMK Bina Nusantara Ungaran) - Bhakti, Galang Krisnawa; Manuputty, Augie David (Journal of Information System and Informatics, 2021)
Business competition in this fast-paced information age has become very tight. especially in the field of education. Thus the organization must have a business strategy that is very mature in order to face the competition. The application of information systems and technology has become one of the most influential business strategies for staying in competition. Bina Nusantara Vocational School has implemented an information system and technology, but apparently it has not run optimally because some parts have not yet implemented an information system. In this study discusses how to plan an IS / IT strategy using ward and peppard methods with supporting analyzes such as Value Chain Porter's, SWOT, and McFarlan's Strategic Grid. Which produces a portfolio of IS / IT that is aligned with the vision and mission and roadmaps of its implementation to support the business processes that are run and make the Bina Nusantara Vocational School excel in education.